Molecular characterization of methicillin-resistant Staphylococcus aureus isolated from a Brazilian university hospital - Martins, Andre [UNESP]; Moraes Riboli, Danilo Flavio [UNESP]; Pereira, Valeria Cataneli [UNESP]; Cunha, Maria de Lourdes Ribeiro de Souza da [UNESP] (Contexto, 2014)
The aim of this study was to perform SCCmec typing in Staphylococcus aureus isolates and to characterize the clonal profile of these isolates. Forty-six mecA gene-positive strains isolated between 2002 and 2006 were submitted to antimicrobial resistance testing by the E-test, SCCmec typing by multiplex PCR, and clonal profile analysis by pulsed-field gel electrophoresis. Forty-one (89.1%) isolates were typed as SCCmec III and five (10.9%) as SCCmec IV. Four circulating clones were detected, one of them comprising isolates related to the Brazilian epidemic clone. This clone was detected throughout the study period. The SCCmec III isolates were associated with a high rate of multidrug resistance and clonal dissemination of methicillin-resistant S. aureus in the wards of the University Hospital of the Botucatu School of Medicine, Universidade Estadual Paulista. (C) 2013 Elsevier Editora Ltda. All rights reserved.
Keywords: Staphylococcus aureus; MRSA; SCCmec; BEC